Mechanism investigation of friction-related effects in single point incremental forming using a developed oblique roller-ball tool - Lu, B.; Fang, Y.; Xu, D.K.; Chen, J.; Ou, H.; Moser, N.H.; Cao, J. (Elsevier, 2014)
Single point incremental forming (SPIF) is a highly versatile and flexible process for rapid manufacturing of complex sheet metal parts. In the SPIF process, a ball nose tool moves along a predefined tool path to form the sheet to desired shapes. Due to its unique ability in local deformation of sheet metal, the friction condition between the tool and sheet plays a significant role in material deformation. The effects of friction on surface finish, forming load, material deformation and formability are studied using a newly developed oblique roller ball (ORB) tool. Four grades of aluminum sheet including AA1100, AA2024, AA5052 and AA6111 are employed in the experiments. The material deformation under both the ORB tool and conventional rigid tool are studied by drilling a small hole in the sheet. The experimental results suggest that by reducing the friction resistance using the ORB tool, better surface quality, reduced forming load, smaller through-the-thickness-shear and higher formability can be achieved. To obtain a better understanding of the frictional effect, an analytical model is developed based on the analysis of the stress state in the SPIF deformation zone. Using the developed model, an explicit relationship between the stress state and forming parameters is established. The experimental observations are in good agreement with the developed model. The model can also be used to explain two contrary effects of friction and corresponding through-the-thickness-shear: increase of friction would potentially enhance the forming stability and suppress the necking; however, increase of friction would also increase the stress triaxiality and decrease the formability. The final role of the friction effect depends on the significance of each effect in SPIF process.